2019
DOI: 10.2478/caim-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

An inversion method based on random sampling for real-time MEG neuroimaging

Abstract: The MagnetoEncephaloGraphy (MEG) has gained great interest in neurorehabilitation training due to its high temporal resolution. The challenge is to localize the active regions of the brain in a fast and accurate way. In this paper we use an inversion method based on random spatial sampling to solve the real-time MEG inverse problem. Several numerical tests on synthetic but realistic data show that the method takes just a few hundredths of a second on a laptop to produce an accurate map of the electric activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We point out that although the average of 10 runs is poor from a statistical viewpoint, it is a good compromise between accuracy and computational cost. In [20] the authors investigated how the increasing of the number of runs up to 50 affects the localization accuracy. They found that accuracy does not improve significantly as the number of runs increases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We point out that although the average of 10 runs is poor from a statistical viewpoint, it is a good compromise between accuracy and computational cost. In [20] the authors investigated how the increasing of the number of runs up to 50 affects the localization accuracy. They found that accuracy does not improve significantly as the number of runs increases.…”
Section: Discussionmentioning
confidence: 99%
“…Another beamforming method, Truncated Singular Value Decomposition Beamformig (TSBF), presented in [30] was proved to give good results when used for the solution of the MEG inverse problem (cf. [20]). For all the methods, the computation of the inverse solution is given by J = Q B where Q is the inverse kernel of the method.…”
Section: The Meg Inverse Problemmentioning
confidence: 99%
See 3 more Smart Citations